Wide Geriatric Assessment of elderly on hemodialysis: case report - Borges, Sheila (2020)
The aim of the study was to assess the nutricional status and describe the results of the tools of the Wide Geriatric Assessment applied in an elderly on hemodialysis, by the nephrology unit of the Distrito Federal. Mild to moderate cognitive degeneration, malnutrition and risk of sarcopenia were found in the patient, enough for the establishment of therapeutic measures with the multiprofessional approach. Keywords: Geriatric Assessment; Elderly; Renal dialysis.